10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Menke-Hennekam syndrome types 1 and 2 (MKHK1 and MKHK2) are autosomal dominant neurodevelopmental disorders characterized by psychomotor developmental delay, intellectual disability, and dysmorphic features. MKHK1 is caused by heterozygous variants in exons 30-31 of the CREBBP gene, whereas MKHK2 results from heterozygous variants in EP300. Although these genes are classically associated with Rubinstein-Taybi syndrome (RTS), Menke-Hennekam syndrome presents a distinct phenotype despite involvement of the same alleles. We report 2 patients who exhibited developmental delay, intellectual disability, and dysmorphic features without typical RTS findings. Genetic analysis revealed a novel frameshift variant in EP300 in one patient and a de novo missense variant in CREBBP in the other. Long-term follow-up and increasing use of whole-exome sequencing have facilitated recognition of Menke-Hennekam syndrome as a distinct clinical entity. Reporting 2 patients with exon 31 variants in CREBBP and EP300, we aim to improve awareness and diagnostic accuracy of this rare disorder.